Pola Komunikasi Guru-Murid di Kelas dalam Perspektif Teori Empat Wacana Lacan - Supratiknya, Augustinus; Hartoko, Victorius Didik Suryo; Suprawati, Maria Magdalena Nimas Eki; Harimurti, Albertus (Fakultas Psikologi Universitas Sanata Dharma, 2023)
The essence of education is communication between educators and students. Teaching as a school education practice has two aspects, namely informative in the framework of forming skills and formative in the context of forming the personality of students. This current study aims to reveal the formative aspects of teacher-student communication patterns in the context of learning subjects in class based on Lacan's Theory of the Four Discourses. The research participants consisted of teachers and students of grades IV and V as class units who were carrying out Social Sciences lessons in three elementary schools in Yogyakarta. Data were collected through audio recordings of teacher-student communication in class. Data were transcribed and analyzed by four researchers separately, the results were discussed to find emerging themes derived from Lacan's Theory of the Four Discourses. The results showed that three types of Lacanian discourse emerged in teacher-student communication in the three schools studied, namely Discourse of the Master, Discourse of the University, and Discourse of the Analyst. This research will be followed up with research on the types of Lacanian discourse that are applied in writing textbooks for subjects in elementary schools including but not limited to Social Sciences.